The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.55133/eji.290404
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry assessment of monocyte subsets alteration in hepatocellular carcinoma post hepatitis C virus infection

Abstract: Hepatocellular carcinoma (HCC) is assumed to be an immunogenic malignancy since 90% of cases develop in environments with ongoing inflammation. Monocyte subsets contribute to tumoral immunity. Most HCC patients are discovered at late stages, which lowers their survival chances. We aimed to determine whether altered frequency of monocyte subsets contribute to post hepatitis C virus infection-liver cirrhosis (HCV-LC) development to HCC. This cross-sectional study enrolled 105 patients classified as post HCV-HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This would support the potential interest of blood monocytes in monitoring LC development and its progression to HCC. In the same line, our recent research revealed an alteration of intermediate monocytes subset in LC and HCC [34].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This would support the potential interest of blood monocytes in monitoring LC development and its progression to HCC. In the same line, our recent research revealed an alteration of intermediate monocytes subset in LC and HCC [34].…”
Section: Introductionmentioning
confidence: 54%
“…Regarding ROC curve analysis, hsa-miR-21-5p was shown to be superior to hsa-miR-155-5p as a plasma molecular marker for identifying LC cases from healthy cases and combining both hsa-miR-21-5p + hsa-miR-155-5p provided an accepted discriminative sensitivity for HCC cases identi cation from LC [34]. Moreover, logistic regression analysis proved that circulating classical and intermediate monocytes frequencies% and hsa-miR-21-5p were independent predictors of HCC progression from cirrhotic background after adjustment for the confounders (age, BMI, RBS, AFP, and lipids).…”
Section: Discussionmentioning
confidence: 98%
“…This would support our potential interest in blood monocytes for monitoring LC development and its progression to HCC. In the same line, our recent research revealed an alteration of intermediate monocytes subset in LC and HCC (Ali et al 2022 ).…”
Section: Introductionmentioning
confidence: 66%
“…Percentage of monocytes subsets was determined from the total monocyte gate, and accordingly, the frequency of the monocytes subsets from the total events acquired was detected. The gating strategy is following the steps of our previous publication Ali et al ( 2022 ). Gating strategy and an example of each patients group are displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the harvested cells were resuspended in 100 µm annexin V binding buffer (Dojindo, Kumamoto, Japan) supplemented with 1% annexin V-FITC. Flow cytometry analysis was then performed on these cells using BD FACSCanto II (NJ, USA) [31] .…”
Section: Flow Cytometrymentioning
confidence: 99%